Low versus High Fluence Parameters in the Treatment of Facial Laceration Scars with a 1, 550 nm Fractional Erbium-Glass Laser. (7th July 2015) - Shim, Hyung-Sup; Jun, Dai-Won; Kim, Sang-Wha; Jung, Sung-No; Kwon, Ho
Abstract : Purpose . Early postoperative fractional laser treatment has been used to reduce scarring in many institutions, but the most effective energy parameters have not yet been established. This study sought to determine effective parameters in the treatment of facial laceration scars. Methods . From September 2012 to September 2013, 57 patients were enrolled according to the study. To compare the low and high fluence parameters of 1, 550 nm fractional erbium-glass laser treatment, we virtually divided the scar of each individual patient in half, and each half was treated with a high and low fluence setting, respectively. A total of four treatment sessions were performed at one-month intervals and clinical photographs were taken at every visit. Results . Results were assessed using the Vancouver Scar Scale (VSS) and global assessment of the two portions of each individual scar. Final evaluation revealed that the portions treated with high fluence parameter showed greater difference compared to pretreatment VSS scores and global assessment values, indicating favorable cosmetic results. Conclusion . We compared the effects of high fluence and low fluence 1, 550 nm fractional erbium-glass laser treatment for facial scarring in the early postoperative period and revealed that the high fluence parameter was more effective for scar management.